PENINGKATAN DAYA SAING INDUSTRI KECIL MENENGAH (IKM) DALAM MENDUKUNG PEMULIHAN EKONOMI DI KABUPATEN SIDOARJO - Heri Soesanto; Sa’adah Sa’adah; Fitriyatus Sholihah; Munari Kustanto (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Small Medium Industries (SMI) play a very important role in efforts to recover the economy after the Covid-19 pandemic. This study aims to analyze competitiveness and formulate strategies to increase the competitiveness of SMI in Sidoarjo Regency in supporting economic recovery. This study uses a quantitative approach with SWOT analysis. The results of the analysis show that 83.5% of SMIs in Sidoarjo Regency are competitive at the local/regional level, 15.5% of SMIs are at the national level, only 1% have global competitiveness. The Sidoarjo Regency Government needs to implement various strategic policies in order to increase the competitiveness of SMIs so that they can make an optimal contribution to economic recovery. Strategies that can be taken start from mentoring, establishing cooperation with the banking sector, to formulating regulations that are able to protect SMIs in Sidoarjo Regency.